Third-Generation Anti-CD47-Specific CAR-T Cells Effectively Kill Cancer Cells and Reduce the Genes Expression in Lung Cancer Cell Metastasis - Huyen Thi La; Dao Bich Thi Tran; Hai Manh Tran; Linh Trong Nguyen (Journal of Immunology Research)
CD47 is a cell surface glycoprotein molecule, belonging to the immunoglobulin superfamily, binding to various proteins including integrins, thrombospondin-1, and signal regulatory protein α (SIRPα). CD47 is an important tumor antigen for the development and progression of various cancers. This study designed the chimeric antigen receptor T-cell (CAR-T) to bind to the CD47 to inhibit the expression of CD47. We used the complementarity-determining regions (CDRs) of the B6H12 mouse antibody grafted onto the IgG1 framework to create the humanized single-chain variable fragment (scFv) with linker (G4S)x3. scFv was used to design the chimeric antigen receptor with the structure CD8signal-CD47scFv-CD8a hinge-CD4TM-CD28-41BB-CD3ζ, which was then transformed into T lymphocytes by the lentivirus to create third generation of CAR-T. Results revealed that the new CAR-T cells efficiently killed A549 cancer cells. CAR-T inhibited the expression of genes involved in metastasis and invasion of cells A549 including beta actin, calreticulin, and cyclooxygenase 2 at mRNA levels.